Sosialisasi Produk Intelektual melalui Pendaftaran Hak Cipta di MA Tijarotal Lantabur - Masagus Firdaus; Bukman Lian; Tri Widayatsih; Tahrun Tahrun; Mulyadi Mulyadi; Hanni Yukamana; Sri Wahyu Indrawati; Nurlina Nurlina; Yudi Irwansi; Suherman Suherman (Jurnal Kemitraan Masyarakat, 2025)
Copyright protection is a crucial aspect in providing legal recognition and guarantees for intellectual property. However, understanding of copyright among educators and students remains limited, potentially leading to violations and a lack of appreciation for copyrighted works. This situation highlights the urgent need for comprehensive education in educational settings, particularly at MA Tijarotal Lantabur. This community service activity aims to improve teachers' and students' understanding of the concept of copyright, the benefits of registration, administrative procedures, and the legal protection provided by the state. Furthermore, this activity is expected to foster awareness of respect for intellectual property and encourage independent copyright registration initiatives. The methods used were interactive lectures, group discussions, and online copyright registration simulations through the Directorate General of Intellectual Property (DJKI) system. The material was delivered in simple and applicable language to ensure participants' understanding. Evaluation was conducted by comparing participants' understanding before and after the activity. The results of the activity showed a significant increase in participants' understanding of copyright concepts and procedures. Participants not only understood the benefits of legal protection for intellectual property but were also able to practice the registration steps independently. Furthermore, a collective awareness emerged to disseminate the acquired knowledge to colleagues and the school environment. Overall, this activity succeeded in increasing legal literacy regarding copyright among teachers and students, and is expected to be able to form a culture of respect for intellectual works while minimizing copyright violations in the educational environment.